The effects of macrolides in children with reactive airway disease: a systematic review and meta-analysis of randomized controlled trials - Lei WT; Lin HH; Tsai MC; Hung HH; Cheng YJ; Liu SJ; Lin CY; Yeh TL (Dove Medical Press, 2018)
Wei-Te Lei,1 Hsin Hui Lin,2 Mu-Chieh Tsai,1 Hua-His Hung,1 Yu-Jyun Cheng,1 Shu-Jung Liu,3 Chien Yu Lin,1 Tzu-Lin Yeh4 1Department of Pediatrics, Hsinchu MacKay Memorial Hospital, Hsinchu, Taiwan; 2Department of Family Medicine, Taipei Mackay Memorial Hospital, Taipei, Taiwan; 3Department of Medical Library, MacKay Memorial Hospital, Tamsui Branch, New Taipei City, Taiwan; 4Department of Family Medicine, Hsinchu MacKay Memorial Hospital, Hsinchu, Taiwan Purpose: Childhood reactive airway diseases (RADs) are concerning problems in children’s airways and may be preceded by bronchiolitis and may progress to childhood asthma. The severity of the disease is indicated by deterioration in pulmonary functions, increased usage of rescue medications, and recurrent wheezing episodes. Macrolides have both antimicrobial and anti-inflammatory functions and have been used as adjunctive therapy in childhood RADs. Patients and methods: We conducted a meta-analysis to evaluate the effect of macrolides in children with RAD. Literature searches were systematically conducted using an electronic database from inception to August 2018. The Cochrane review risk of bias assessment tool was used to assess the quality of each randomized controlled trial. Results: Sixteen randomized controlled trials comprising 1,415 participants were investigated in this meta-analysis. Children treated with macrolide therapy showed significantly better pulmonary functions in both forced expiratory volume in one second (% predicted) (difference in means=-9.77, 95% CI=-14.18 to -5.35, P<0.001; I2=0%) and forced expiratory flow 25–75 (% predicted) (difference in means=-14.14, 95% CI=-26.11 to -2.18, P=0.02; I2=29.56%). In addition, the short-acting ß-agonist usage days and recurrent wheezing risk were significantly lowered in children with macrolide treatment (standardized difference in means=-0.34, 95% CI=-0.59 to -0.09, P=0.007, I2=27.05% and standardized difference in means=-0.53, 95% CI=-0.81 to -0.26, P<0.001, I2=0%, respectively). Furthermore, the growth of Moraxella catarrhalis from nasal swabs was less in children treated with macrolides (odds ratio=0.19, 95% CI=0.11–0.35, P<0.001). Children who took macrolides had a lower risk of adverse events (risk ratio=0.83, 95% CI=0.70–0.98, P=0.024, I2=0%). Conclusion: This current meta-analysis suggested that adjunctive therapy with macrolides is safe and effective for achieving better outcomes in childhood RAD. Keywords: macrolides, childhood, asthma, recurrent wheezing, bronchiolitis, pulmonary function, efficacy, reactive airway disease